The Effect of Amorphous Silica Residue in the Production of Concrete - Mbadike, Elvis M; Osadebe, N N (International Journal of Sustainable Construction Engineering and Technology, 2013)
In this research work, the effect of amorphous silica residue (ASR) in the production of concrete was investigated. A mix proportion of 1:1.9:3.9 with water/cement ratio of 0.48 was used. The percentage replacement of Ordinary Portland Cement (OPC) with amorphous silica residue was 0%, 5%, 10%, 20% and 30%. Concrete cubes of 150mm x 150mm x 150mm and concrete beams of 150mm x 150mm x 600mm of OPC/ASR were cast and cured at 3, 7, 28, 60 and 90 days. At the end of each hydration period, the three concrete cube and beams for each hydration period were crushed and their average compressive and flexural strength recorded. A total of seventy five (75) concrete cubes and seventy five (75) concrete beams were cast. The result of the compressive strength test for 5-30% replacement of cement with amorphous silica residue ranges from 12.78-38.16N/mm2 while the control test (0% replacement) ranges from 10.86-26.04N/mm2. The result of the flexural strength test for the same replacement level of cement with amorphous silica residue ranges from 2.29-11.69N/mm2 while the control test ranges from 2.14 – 7.80N/mm2. The initial setting time of OPC/ASR for 5-30% replacement level of cement with amorphous silica residue ranges from 37-53mins while the final setting time ranges from 408-573mins. The initial and final setting time of the control test is 58mins and 580mins respectively. Relevant literature has been cited to justify this research work. The main objective of this work is to determine the effect of amorphous silica residue on the setting time, compressive strength and flexural strength of concrete produced with it.